Integration of Advanced Analytical Techniques and Data Management Systems in Modern Research Laboratories: A Comprehensive Review of Technician Roles and Competencies - Mohammed Ahmed Alabdrabalredha,; Mohammed Abdullah Hussain Aldandan,; Murtada Abdullah Eid Al Habeeb,; Haidar Ali Alhajji Mohammed,; Amirah Helal A Al Helal, (International Journal of Medical Toxicology and Legal Medicine, 2024)
The integration of advanced analytical techniques and data management systems has revolutionized modern research laboratories, necessitating the evolution of technician roles and competencies. This comprehensive review explores the impact of these technological advancements on the responsibilities and skill sets required of laboratory technicians. A systematic literature search was conducted using multiple databases, including PubMed, Scopus, and Web of Science, to identify relevant studies published between 2010 and 2022. The search yielded 85 articles that met the inclusion criteria, which were then subjected to a thorough analysis and synthesis. The findings reveal that laboratory technicians play a pivotal role in the successful implementation and utilization of advanced analytical techniques, such as high-performance liquid chromatography, mass spectrometry, and next-generation sequencing. Additionally, technicians are increasingly involved in data management, including data acquisition, processing, storage, and analysis, using sophisticated software tools and platforms. The review highlights the need for continuous training and professional development to ensure that technicians possess the necessary technical, analytical, and data management skills to operate effectively in modern research laboratories. Furthermore, the study emphasizes the importance of collaboration and communication skills, as technicians often work in multidisciplinary teams and interact with researchers, scientists, and other stakeholders. The findings of this review have significant implications for laboratory management, technician training programs, and the overall advancement of scientific research in the era of big data and advanced analytical technologies.